Isolation of Lactobacilli from Freshly Drawn Raw Milk of Desi and Crossbred Cows of Gurugram Region, Haryana - P, Prachi; Khunger, Sandhya; Kumar, Sunil; Sharma, Mukesh; Mudgal, Mukul (Asian Journal of Biological and Life Sciences)
Background: Cow milk is of great concern these days because of its high nutritional value as well as the probiotic flora present in it, which confer several benefits to the human body. Lactobacillus is one such beneficial bacterium present in milk that helps the human body against allergic reactions, gastrointestinal diseases, and irritable bowel. Aim: The current study aims to determine the prevalence and isolation of Lactobacillus present in milk. The raw cow milk samples were collected from two categories of cows: desi cows and cross-breed cows. Raw cow milk is said to be harmful for human consumption due to the presence of pathogenic microflora. Materials and Methods: The raw cow milk samples were cultured on MRS agar (selective media) to isolate the diversity of Lactic acid bacteria (LAB) present in cow milk as probiotic flora. A total of twelve milk samples were taken; 5 from the cross-breed cows and 7 from the desi cows. Samples were cultured on MRS agar anaerobically for 24-48 hours. The bacterial isolates were tested for morphological characters, and biochemical tests including catalase, oxidase, citrate, sulfide, indole motility, and tolerance at physiological conditions like growth at different temperatures (ranging from 25- 450C), growth in different saline concentrations (2%, 4%, 6%, 8%, and 10%), and growth in different pH (4, 5, 6, 7, 8). Result: At the end of the study, three isolates were found gram-positive rods, out of which, 2 were catalase-negative and one was catalase-positive. All three strains were able to tolerate some physiological conditions. Conclusion: These can be further used as preservatives in some food items to increase their nutritional value as well as for further molecular studies for the identification of particular Lactobacillus species. Some new strategies should be implemented to make more efficient identification of LAB strains.
Keywords: Biochemical Tests; Lactobacillus; Natural source; Physiological Tolerance; Probiotics; Raw Milk